THE EFFECTIVENESS OF SUPERVISION ON ISLAMIC EDUCATION (PAI) TEACHER'S PERFORMANCE OF JUNIOR HIGH SCHOOL (SMP) IN PANGKALPINANG - Mardiyah, Sri (Berumpun: International Journal of Social, Politics and Humanities, 2019)
This paper is based on the many problems that occur in the implementation of the supervision of teaching junior high school Islamic education in the city of Pangkalpinang. Teaching supervision as a form of assistance and guidance to teachers to develop their abilities in the learning process has not been giving a significant impact in improving the quality of Islamic Education (PAI) learning. For this reason, a qualitative descriptive study was conducted on two state junior high schools that had different characters and qualities. Data and information are collected through unstructured interviews, unstructured observation, and documentation. Furthermore, the data is processed and analyzed descriptively through interactively as the Miles and Huberman flow models, namely data reduction, data display, and conclusion. The results of data analysis showed that the supervision of PAI teaching in these two schools was still administrative. As a result, teaching supervision tends to be a mere formality and the basic principles have not been properly implemented. Naturally, the supervision of PAI teaching has not had a significant impact on PAI teachers, both due to supervisory competence and teacher readiness. However, there are also factors that are felt to be quite supportive, such as the commitment of supervisors in the midst of the limited number and desire of teachers to develop. Furthermore, based on the disclosure of facts on this issue, it is expected to be the basis of evaluation and efforts to improve the implementation of teaching supervision in the Junior High School in Pangkalpinang City, especially in Islamic Education Subjects.